Analisis Psikomotorik Halus Siswa Ditinjau dari Keterampilan Menggambar Anak Usia Dasar SD - Maulida Rizqia; Wahyu Iskandar; Nurzakiah Simangunsong; Suyadi Suyadi (Al-Aulad: Journal of Islamic Primary Education, 2019)
This article has a purpose to find out the development of the elementary student psychomotor which carried out in SDN Demangan, Yogyakarta. The development is related to the activity using fingers to do a variety of activities such as drawing. This research used descriptive qualitative method and to quest the data it used observation, interviews and documentation method by observing the development of the student psychomotor. The focus of this research is on finding: 1) how the development of the student psychomotor whether it is reached or not, 2) how the factors that affect the development of the student psychomotor, 3) how the solution to the development of the student psychomotor. The result are: 1) the development of the student psychomotor which is reached and not, it is marked by the coordination of nerve and well fingers movement, so the student obtains the result of the good drawing, 2) the factor that affects the development of the student psychomotor, there are two factors; internal and external. Internal factor is influenced from genetic factor and the external is from the surrounding environment to support the development, 3) the solution is to anticipate the problems of the development of the student psychomotor by seeking the training and giving guidance toward the student to motivate them achieving the development.Keywords: Development, psychomotor, children, elementary school